Effect Of Operating Conditions On Steady-State Behavior Of Activated Sludge In Phenolic Waste Water Treatment - B. T. Basuki (Reaktor, 2005)
Steady-state behavior of activated sludge in phenolic waste water treatment was observed and theoretically considered. The apparatus used in  this experiment was a continuous perfect mixing tank where activated sludge was withdraw continuosly and auto-returned from a settling tank. To explain the data well, it must be taken into  consideration that activated sludge consist of various species of microorganisms. Therefore, ecosystem and whole metabolism of activated sludge would be effected not only by environmental condition (pH, temperature, DO,etc.), but also by operating variables (dilution rate, inlet substrate concentration, etc.). In this study, the relation of whole metabolism of activated sludge between the case which activated sludge is regarded as various species of microorganisms was obtained. Seven empirical parameters in the kinetic equation which were introduce from the predator-prey interaction model were considered to be a function of various operating variables. By using this method, steady-state behavior of activated sludge in the ohenolic waste water treatment could be well explained, moreover, important information to design a practical process for phenolic waste water treatment with activated sludge was obtained.Keywords : phenolic waste water treatment, activated sludge, effect of operating conditions, predator-prey interaction model, kinetic model